Diversidade beta taxonômica e funcional de Rotifera em quatro grandes planícies de inundação neotropicais, Brasil. - Delgado, Tayná de Almeida (2023)
The taxonomic and functional beta diversity of rotifers in floodplains can help understand responses to environmental changes as well as ecosystem dynamics. The taxonomic and functional beta diversity of rotifers was analyzed in four neotropical floodplains (Amazonas, Araguaia, Pantanal, Paraná River), in order to verify whether there are differences in the composition and structure of the rotifer community in the different plains and within each plain between the different periods. Differences in taxonomic and functional beta diversity were tested using multivariate statistics. 128 species of rotifers were identified, 84 in the Paraná River, Amazonas (78), Araguaia (77) and Pantanal (75). Functionally equal species were grouped together. The plains of the Paraná and Amazon rivers were those that showed a significant difference in taxonomic and functional beta diversity during the rainy season. During the dry period, the plains that showed differences were Araguaia and Amazonas and the Paraná and Araguaia rivers. Functional beta diversity did not show a significant difference during the dry period. Changes in taxonomic beta diversity can result in long-term loss of ecosystem function, potentially altering its functioning. Therefore, the study of taxonomic beta diversity must be followed by functional beta diversity to better understand the dynamics and functioning of the ecosystem, as well as its preservation.